Open for business: Pathways to strengthen CGIAR's responsible private sector engagement - Cummings, Sarah; Koerner, Jana; Schut, Marc; Lubberink, Rob; Minh, Thai Thi; Spielman, David J.; Vos, Janny (CGIAR, 2022)
CGIAR has considerable experience with private sector engagement in the context of its mission to create sustainable and resilient food, land and water systems, and there is continuing interest and dialogue on this theme within CGIAR and the international development community more generally. The on-going CGIAR reform provides an opportunity to capture those experiences and harmonize strategies under the new structure, as has been acknowledged in the new ‘CGIAR 2030 Research and Innovation Strategy’. Commissioned by the NL-CGIAR Strategic Partnership, this report aims to identify, discuss and evaluate pathways for strengthening collaboration between CGIAR and the private sector to stimulate innovation and the scaling of these innovations in food, land and water systems. The objective is to advance private sector engagement in the CGIAR, based on transparent CGIAR system-wide mechanisms and processes.